Transformación integral e industrialización del saúco (sambucus peruviana) para el desarrollo microregional sostenible - Verde García, Peter T. (2006)
In the present work an activity is determined leaves from the Integral Transformation and Industrialization of Saúco (Sambucus Peruviana HBK) for Sustainable the Microregional Development of our mountainous area. In one of the industrialization alternatives is on the use of its antimicrobial activity and from the active principles of Saúco (Peruviana Sambucus HBK) dry extracts (watery, metabolic and etanólico) of the flowers were obtained, leaves and fruits of the plant. The antimicrobial activity determined by means of the Method Excavation Plate Culture in front of stocks of sensible microorganisms, the active components determined with the Methods of March Fitoquímica and Cromatografi'a of descendent paper and fine Layer. The extracts of the flowers and leaves presented/displayed antimicrobial activity forehead a: Salmonella Typha ATCC 11011, Salmonella paratyphi ATCC 25923, Klebsiella pneumoniae ATCC 10031, Shiquella dysenteriae ATCC 25912 and staphylococcus aureus ATCC 23923. This activity a was not observed in front: Saccharomyces 10232 cerevisiae ATCC and Candida albicans ATCC 10371. The extracts of the fruit did not show to antimicrobial activity some. The present active principles in the elder tree (Peruviana Sambucus HBK) were: tannins, flavonoides, saponinas, steroids, alkaloids, mucilagos, catequinas, quinonas, lactoses, cumarinas and antocianidinas. The groups of found flavonoides were flaconas, charconas, antocianinas, flavonoles, flavanonas and catequinas